Exploring National Challenges in Learning English Speaking: Focussing on Solving Chinese Learning Challenges Through a Functional Grammatical Approach - Gong, Shiqiao (Trinity College (Dublin, Ireland). School of Education, 2021)
Many Chinese students have difficulties in expanding their meaning in English speaking. Why they meet these difficulties and how to solve Chinses students’ problems are the driving focuses of this thesis. In chapter two, the speaking problem of Chinese students was partially solved by Communicative Language Teaching conducted in the last thirty years, but the result is not fully positive. By taking an international view, countries in Europe and Asia were selected to present the different linguistic features between English and other languages in chapters four and five. A comparison between Chinese and English is described in chapter six. In chapter seven, Functional Grammar was introduced in China and has been developed theoretically for many years. Transitivity theory, as one main concepts of Functional Grammar, can help learners to expand meaning in communication, but it is only suitable for elementary learners since context and interpersonal relationships should also be considered. More empirical data and applications are needed in the future.
Keywords: Language Studies; Education